Cultural heritage as activator of circular urban dynamics - Rossella Roversi; Danila Longo; Martina Massari; Serena Orlandi; Beatrice Turillazzi (Techne, 2021)
Cultural heritage can represent a key factor in circular processes on an urban scale that trigger relationships between users and the surrounding environment, generating new urban capital and enhancing individual and collective capacities. This topic is addressed through a review of academic literature and policy documents and a comparative analysis of two regeneration processes carried out in the cities of Bologna and Bogotà: the H2020 ROCK – Regeneration and Optimisation of Cultural Heritage in creative and Knowledge cities (GA 730280) project – on the historical university area, and the experiments on the former Ravone railway station of the OBRAS – Opportunities for Boosting urban capabilities project – developed in parallel on the La Sabana Station in Bogotá, Colombia.